Răspuns :
m+a=60
m=60-a
2m+5a=180
2(60-a)+5a=180
120-2a+5a=180
-2a+5a=180-120
3a=60
a=60:3
a=20
m=60-a
m=60-20
m=40
m=60-a
2m+5a=180
2(60-a)+5a=180
120-2a+5a=180
-2a+5a=180-120
3a=60
a=60:3
a=20
m=60-a
m=60-20
m=40
Notam: Mihai=m
Alin=a
m+a=60lei
2m+5a=180lei
2(m+a)+ 3a=180lei
2*60lei+3a=180lei
120lei+3a=180lei
3a=180-120lei
3a=60lei
a=60lei/3
a=20lei
m=60lei-a= 60lei-20lei= 40lei
Alin=a
m+a=60lei
2m+5a=180lei
2(m+a)+ 3a=180lei
2*60lei+3a=180lei
120lei+3a=180lei
3a=180-120lei
3a=60lei
a=60lei/3
a=20lei
m=60lei-a= 60lei-20lei= 40lei